GW24-e2989 Linear ablation of left atrium for treatment atrial fibrillation guided by three dimensional electroanatomical mapping but without lasso catheter. (1st October 2013) - Li, JuXiang; Hu, jianxin; Shu Cheng, Xiao; Raatikainen, Pekka; juxiang, Li
Abstract : Objectives: There were few data about linear ablation of left atrium (LA) without lasso catheter guiding, We report the results of linear ablation of LA guided by three dimensional (3-D) electroanatomical mapping (Carto) and mapping catheter but without lasso catheter in 106 patients. Methods: There were 106 patients (mean age, 51.4 ± 9.9 years). Seventy-eight patients had paroxysmal AF, 12 persistent AF and 16 permanent AF. After the anatomical model of LA and all pulmonary veins (PVs) had been established, circumferential ablations of the left pulmonary vein antrum and the right pulmonary vein antrum were performed. The endpoint of ablation was abolishment or dissociation of the pulmonary vein potentials (PVPs) according to the mapping at the two sides of ablation line with large-tip mapping catheters. Oral amiodarone or Flecainide was taken for at least 3 months by patients with persistent AF, or those whose PVPs had not been isolated completely. The recurrence of atrial tachyarrhythmia was observed 3 months after the procedure. Results: Onset of atrial fibrillation occurred in 52 patients during ablation procedure. Thirty-two patients restored to sinus rhythm eventually after the procedure. Abolishment or dissociation of PVPs was accomplished during the procedure in 94 patients (88.7%). The duration of procedure and exposure to X-ray were (213 ± 45) minutes and (32.5 ± 12.8) minutes, respectively. Among the 87 patients followed up for over 3 months, 62 were free of atrial tachyarrhythmias (including 8 patients who were still taking oral amiodarone). The success rate was 71.3% in the first procedure. Two patients had pericardial effusion treated by pericardial puncture and effusion drainage. No pulmonary vein stenosis, atrioesophageal fistula, pericardial effusion, stroke or procedural death occurred. Conclusions: Combination of 3-D electroanatomical mapping with large-tip catheter mapping at two sides of ablation line to guide the linear ablation of left atrium procedure can confirm the isolation of PVPs.